INGRESO POR REMUNERACIONES EXTRAORDINARIAS, COMISIONES Y MULTAS DEL PERSONAL CENTER DRIVE - LAROSA CORTEZ, CRISTHOPER ORLANDO (2018)
he Center Drive school receives its operating permit to conduct the training in the city of Babahoyo on March 6, 2008 prior to compliance with the provisions of the regulations of training schools, under this context and after the analysis of the corresponding documentation , as well as the respective technical inspection report, No. 012- CNTT-2008 dated February 28, 2008, that permit is granted.